Tension-type Headache and Migraine as Manifestations of Chronic Post-Traumatic Headache - Eric Hartono Tedyanto; -I Made Oka Adnyana; I Putu Eka Widyadharma (Cermin Dunia Kedokteran, 2023)
Introduction: A subsequent headache within seven days of a head injury (or after regaining consciousness after the head trauma)is referred to as a post-traumatic headache (PTHA); it is referred to as chronic or chronic post-traumatic headache (CPTHA) if it lasts longer than three months after the injury. Case : A 17-year-old male with headache since 3 months ago, 3 days after suffered a blow to his left head from falling from a chair. At that time, the patient fainted for about 15 minutes but had no complaints after regained consciousness. Pain is felt on the left side of the head, throbbing, mild-moderate intensity, and feels heavier with a loud sound or a too-bright light. Discussion: Post-traumatic headache is clinically diagnosed. Laboratory and routine diagnostic imaging studies are unnecessary and have minimal clinical utility. Conclusion: Chronic post-traumatic headaches often occur, especially after minimally traumatic brain injury. The clinical picture is variable and may be similar to tension-type headaches and/or migraines.   Pendahuluan: Nyeri kepala dalam tujuh hari setelah cedera kepala atau setelah sadar kembali dari trauma kepala disebut nyeri kepala pasca-trauma (post-traumatic headache/PTHA); disebut sakit kepala pasca-trauma kronis atau kronis (CPTHA) jika berlangsung lebih dari tiga bulan setelah cedera. Kasus: Seorang laki-laki berusia 17 tahun dengan keluhan nyeri kepala sejak 3 bulan, 3 hari setelah kepala kiri terbentur karena jatuh dari kursi. Saat itu, pasien pingsan sekitar 15 menit, tidak ada keluhan setelah sadar. Nyeri dirasakan di sisi kiri kepala, berdenyut, intensitas ringan-sedang, terasa lebih berat jika ada suara keras atau cahaya terlalu terang. Diskusi: Nyeri kepala pasca-trauma didiagnosis secara klinis. Laboratorium dan studi pencitraan diagnostik rutin tidak diperlukan dan memiliki utilitas klinis minimal. Simpulan: Nyeri kepala pasca-trauma kronis sering terjadi, terutama setelah cedera otak traumatis minimal. Gambaran klinisnya bervariasi dan dapat mirip nyeri kepala tipe tegang dan/atau migrain